131 Myotonic dystrophy: the interface with palliative medicine, a series of cases. Issue Volume 11: Issue (2021)Supplement 1 (16th March 2021) - Dewhirst, Laura; Bassie, Claire; Young, Ceri; Willis, Derek
Abstract : Background: Myotonic Dsytrophy (DM) is a multi-system disease that affects muscle function. DM is the most common muscular dystrophy occurring in adulthood and the prevalence is around 10 cases per 100, 000. There are two distinct forms Type 1 and Type 2. DM predominantly causes weakness of the voluntary muscles but involuntary muscles can also be affected. As the disease progresses respiratory, cardiac and gastrointestinal symptoms can arise. Despite treatment options for management of complications, DM remains a progressive life limiting condition. Severn Hospice is now affiliated with Robert Jones Agnes Hunt Hospital in Oswestry to provide a symptom control clinic for DM patients; something that is not routinely done nationally. Palliative Care should be involved early in the diagnosis to allow more effective symptom control and discussions around Advance Care Planning. Methods & Results: We collated the data for the 5 patients with a DM diagnosis that were referred to Severn Hospice and/or joint symptom control clinics. All 5 patients were assessed for symptoms that included but were not limited to: breathlessness, pain, dysphagia and low mood. 3/5 patients are still alive and have ongoing support. We coordinated referrals to other specialities including PEG/Respiratory teams for ongoing assessment. 1 patient was admitted to the inpatient unit which allowed for symptoms to be optimised and Advance Care Planning to occur. Conclusions: The role of Palliative Care in the management of DM patients is paramount and early involvement in the disease trajectory is optimal for improving symptom control and providing opportunities for advance care planning relating to specific complications, e.g. cardiac arrhythmias/feeding tube insertion/respiratory support. Clinical guidelines for the role of Palliative Care in DM are limited, despite the fact it is a life limiting illness. This has prompted a focus group who are looking to put together some National Guidance moving forwards.